The Effect of Work Conflict and Work Stress on the Spirit at Work of Local Water Company (PDAM) Employee in South Solok Regency - Suhery Suhery; Agus Nurofik (Yayasan Ilomata, 2020)
This study aims to do understanding: (1) the effect of work conflict to the spirit at work; (2) the impact of work stress on the spirit at work; (3) the effect of a work conflict and work stress to the spirit at work of PDAM employee in South Solok Regency. This research used quantitative research method by casual associative approach. The sampling technique that used was purposive sampling technique with 39 people. The method used to compile data was questionnaire method. The method that used to analyze data in this research was descriptive analysis and multiple linear regression by SPSS programs v 20.0 for windows. Based on multiple linear regression analysis, it was known that the work conflict (X1) has a significant effect on the spirit at work (Y) with beta coefficient 0.283. Work stress (X) has a significant effect on the spirit at work (Y) with beta coefficient 0.631. This result shows that work conflict and work stress have a significant and positive effect on the work spirit of PDAM employee in South Solok Regency with sig. Score F < 5% (0.000 < 0,05). In conclusion, work conflict and work stress are the factors which affect the spirit at work with 61.7%, while the other percentage 38.3% is affected by the other factors which are not becoming research object from this study.